Music Composition “Ngulat-Gedig” | Komposisi Karawitan “Ngulet-Gedig” - I Made Budiartana (GHURNITA: Jurnal Seni Karawitan, 2022)
Ngulat-Gedig is a new musical composition, which means interwoven tones that cross and complement each other to create a strong and beautiful design. This new karawitan composition was created based on the inspiration of the process of weaving bamboo handicrafts, where to get a strong, intact, and beautiful design on each piece of bamboo, it is woven across each other and complements each other, sometimes in harmony, sometimes in contrast, to get a beautiful and strong design. This phenomenon of the bamboo weaving process is transformed into a tangle of beautiful tones into a new, beautiful, strong musical composition with a distinctive identity. The main idea of this work is expresed in an innovative musical using the Gamelan Semarandana. The composition of the Karawitan "Ngulat-Gedig" is realized through a qualitative method through the process of observation, interviews, and literature studies, then the ideas are poured through the stages of exploration, improvisation, and formation.